Understanding the Slow COVID-19 Trajectory of Cambodia - Buntongyi Nit; Alexander Lourdes Samy; Shu Leed Tan; Sopanha Vory; Youhok Lim; Ryan Rachmad Nugraha; Xu Lin; Attaullah Ahmadi; Don Eliseo Lucero-Prisno, III (Elsevier, 2021)
COVID-19 has resulted in large number of mortalities across the globe. However, Cambodia has recorded low number of COVID-19 cases with no death. A number of factors buttress the accuracy of this phenomenon such as significant support from international health partners, culture of wearing a face mask when sick, timely response of Cambodia's neighbouring countries, and the compliance of the general public to the restrictions. Cambodia started to take stringent measures and augmented efforts to initiate policies and plans to curb the spread of the virus, including but not limited to: closure of inbound and outbound borders, shutting down of schools, and banning religious activities, gatherings and meetings, with more than 50 people. Another source of success of Cambodia is extensive mass testing, complemented with contact tracing. A strategy called "box in" the virus was introduced. Healthcare workers were trained to help in contact tracing and detection at the community level. Measures enacted so far has helped Cambodia control the pandemic. Other countries could adopt and adapt to the policies and best practices of Cambodia. However, possibilities of new waves of the pandemic may affect the country, thus, the Cambodian government needs to be cautious when lifting restrictions to avoid explosion of new cases.